Comparative genomic and transcriptional analyses of CRISPR systems across the genus Pyrobaculum - Bernick, David L.; Cox, Courtney L.; Dennis, Patrick P.; Lowe, Todd M. (Frontiers in Microbiology, 2012)
Within the domain Archaea, the CRISPR immune system appears to be nearly ubiquitous based on computational genome analyses. Initial studies in bacteria demonstrated that the CRISPR system targets invading plasmid and viral DNA. Recent experiments in the model archaeon Pyrococcus furiosus uncovered a novel RNA-targeting variant of the CRISPR system potentially unique to archaea. Because our understanding of CRISPR system evolution in other archaea is limited, we have taken a comparative genomic and transcriptomic view of the CRISPR arrays across six diverse species within the crenarchaeal genus Pyrobaculum. We present transcriptional data from each of four species in the genus (P. aerophilum, P. islandicum, P. calidifontis, P. arsenaticum), analyzing mature CRISPR-associated small RNA abundance from over 20 arrays. Within the genus, there is remarkable conservation of CRISPR array structure, as well as unique features that are have not been studied in other archaeal systems. These unique features include: a nearly invariant CRISPR promoter, conservation of direct repeat families, the 5' polarity of CRISPR-associated small RNA abundance, and a novel CRISPR-specific association with homologues of nurA and herA. These analyses provide a genus-level evolutionary perspective on archaeal CRISPR systems, broadening our understanding beyond existing non-comparative model systems.